Living up to Policy Coherence for Development? The OECD's disciplines on tied aid financing - Livia Fritz; Werner Raza (Austrian Foundation for Development Research (ÖFSE), 2014)
With tied aid credits donors aim at boosting the international competitiveness of domestic enterprises while simultaneously contributing to development in recipient countries. Though regulated through the Arrangement on Officially Supported Export Credits, tied aid credits claim a place amongst the instruments of development policy and are eligible as Official Development Assistance (ODA). This begs the question whether the international regulatory framework is equipped to safeguard the presumed development goals. This paper examines the consistency of the tied aid disciplines of the Organisation for Economic Co-operation and Development (OECD) with the development principles coined by the Development Assistance Committee (DAC). Thereby, the extent to which the OECD lives up to its own promise of Policy Coherence for Development (PCD) is scrutinised.
Keywords: 330; policy coherence for development; tied aid; export promotion; OECD/DAC